Kontribusi Wanita Nelayan Dalam Sosiokultural Gender di Kelurahan Pulau Panjang Barelang - Batam - Ely Kartikaningdyah; Chici Ramdaniah; Mega Mayasari (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2013)
Gender is defined as referring to the socio-cultural construction of sex and femininity attitudes, thus allowing the emergence of masculine and feminine characteristics. Gender distribution is limited to the characteristics of men and women were then viewed in terms of social adjustment to the division of tasks and responsibilities. Sociocultural formation according to some experts is formed which is due to the division of tasks and functions that exist in society, this is because of the occurrence of each community to arrive at a balance point that required a division of tasks and functions should be equal between the sexes. The purpose of this study to identify the work that women do in the home of fishermen and fishermen know the contribution of women in the division of labor within the household. Samples taken by 30 households women fishing in Long Island Barelang. The analytical method used is descriptive analysis. Contribution and role of women in the division of tasks and responsibilities in the area of Long Island based on the results of questionnaires that have been outlined in the discussion stated that the work done by women and men have been evenly distributed, this is evidenced by the results of the average percentage distribution of tasks and responsibilities are not equally controlled by women at 100%. In this case there is still a division of the tasks performed by males, although the percentage is still greater contribution of women compared with men. In this research note that the division of labor between men and women in the area of Long Island is not to be a gender bias, as it can be seen that some of the work is not entirely left to the women, but there are also contributions from the men.